The EU deep trade agenda : law and policy - Araujo, Billy A. Melo (Oxford : Oxford University Press, 2016)
Offering a doctrinal analysis of the EU's trade policy, this volume examines the provisions of a generation of new trade agreements in the broader context of EU foreign policy objectives.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 8, 2016).
Keywords: European Union; European Union countries -- Commerce; Industry; Business & Management